2016
DOI: 10.1039/c5ee03045e
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient inverted bulk-heterojunction solar cells with a gradiently-doped ZnO layer

Abstract: Highly efficient inverted BHJ solar cells were demonstrated using a wet-chemically prepared doped ZnO layer with a self-organized ripple nanostructure. The solar cell based on PTB7 and PC71BM with Li2CO3-doped ZnO layer yielded a maximum efficiency of 10.08%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 32 publications
2
51
0
Order By: Relevance
“…Among the PBDTTT derivatives, the representative materials were poly[4,8‐bis[(2‐ethylhexyl)oxy]benzo[1,2‐b:4,5‐b′]dithiophene‐2,6‐diyl][3‐fluoro‐2‐[(2‐ethyl hexyl)carbonyl]thieno[3,4‐b]thiophenediyl]] (PTB7) and poly[[2,6′‐4,8‐di(5‐ethylhexylthienyl)benzo[1,2‐b;3,3‐b]dithiophene][3‐fluoro‐2[(2‐ethylhexyl)carbonyl]thieno[3,4‐b]thiophenediyl]] (PTB7‐Th) (Figure a) . Liang et al reported a high PCE of 7.4% in PTB7:PC 70 BM OSCs .…”
Section: Device Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Among the PBDTTT derivatives, the representative materials were poly[4,8‐bis[(2‐ethylhexyl)oxy]benzo[1,2‐b:4,5‐b′]dithiophene‐2,6‐diyl][3‐fluoro‐2‐[(2‐ethyl hexyl)carbonyl]thieno[3,4‐b]thiophenediyl]] (PTB7) and poly[[2,6′‐4,8‐di(5‐ethylhexylthienyl)benzo[1,2‐b;3,3‐b]dithiophene][3‐fluoro‐2[(2‐ethylhexyl)carbonyl]thieno[3,4‐b]thiophenediyl]] (PTB7‐Th) (Figure a) . Liang et al reported a high PCE of 7.4% in PTB7:PC 70 BM OSCs .…”
Section: Device Efficiencymentioning
confidence: 99%
“…After optimizing the device fabrication of PTB7:PC 70 BM OSCs, He et al reported a dramatically improved PCE of 9.2% . Recently, Nho et al reported a PCE of 10.08% in OSCs based on PTB7 by modifying the device architecture . PTB7‐Th is a modified PTB7 polymer; the 2‐ethylhexyl‐thienyl group was introduced into the BDT moiety, thereby leading to a deeper HOMO with a narrow E g .…”
Section: Device Efficiencymentioning
confidence: 99%
“…[34] Our previousw ork indicated that poly [9,9-bis(4-sulfonatobutyl)-2,7-fluorene]-alt-2,7-(9,9-bis{2-[2-(2-methoxyethoxy)ethoxy]ethyl}fluorene) (PF EO SO 3 Na) with sodium sulfonate and PEO derivatives in the side chains shows excellent electron-transport properties in polymer light-emitting devices and polymers olar cells. [38] These phenomenac an be explained by the fact that Li prefers to be located at Zn sites as an acceptor and simultaneously reduces the density of oxygen at the site because the ionic radius of Li (0.76 )i sv ery closet ot hat of Zn (0.74 ). demonstrated that the intrinsic surfaced efects of ZnO are dramatically restrained if it is doped with as mall quantity of Li.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there have been outstanding improvements, with the power conversion efficiency (PCE) reaching up to 13%. These achievements can be accomplished via the synthesis of efficient conjugated polymers/oligomers or through device engineering …”
Section: Introductionmentioning
confidence: 99%